Intermediate electromagnetic theory - Stewart, Joseph V. (World Scientific, 2001)
This textbook provides a comprehensive introduction to intermediate-level electromagnetic theory. It covers topics such as electric and magnetic fields, electromagnetic waves, boundary conditions, and radiation. Designed for physics and engineering students, the book emphasizes both the mathematical formulation and physical interpretation of Maxwell's equations and their applications in modern science and technology.